JENIS DAN FUNGSI PERMAINAN BAHASA (BAHASA PLESETAN) PADA KAUS YAJUGAYA: SEBUAH TINJAUAN SOSIOLINGUISTIK) - Kinanti, Kingkin Puput; Riskawati, Yuliana (Hasta Wiyata, 2021)
This study aims to describe (1) types of language game and (2) functions of language games on Yajugaya shirts. This type of research is a qualittative descriptive study. The subjects of this research are in lingual units consisting of words, pharases and sentences contained in the Yajugaya shirt. The object of research is the from of language games, types of language games and the funcitions of language games found on the Yajugaya shirt. Data obtained by observation and dokumentation techniques, the technique is applied by collecting sources in the form of language game material especially material that refers to theYajugaya shirt to strengthen the research. Data were analyzed using interactive methods, in the interactive analysis process, there were data collection, data reduction, data presentation, and conclusion drawing. On the validity of the data obtained through the validity test of increasing persistence, triangulation and peer discussion. The results of the study consisted of three thing, namely as follows: first, the basic froms of language games contained in the Yajugaya shirt were 3. Namely (1) basic form of language game words (2) basic forms of language games phrase (3) basic from of language game sentences. The two funcition of language games on the shirt are also 4, namely (1)type of word play on the shirt, (2) types of word games between languages on the Yajugaya shirt, (3) types of malapropism, (4) types of tongue glitch on the Yajugaya shirt. Third, there are 4 funcitions of the language game on the shirt namely (1) humor funcitions (2) criticism funcition (3) creative funcitions and (4) aesthetic funcitions.